1983
DOI: 10.1139/v83-265
|View full text |Cite
|
Sign up to set email alerts
|

Second sphere coordination of phenols, anilines, and benzoic acids to the hexacyanocobaltate(III) anion

Abstract: Can. J. Chem. 61, 1524 (1983. Complexing between the hexacyanocobaltatc(lI1) anion and ten substitutcd phenols, cight substituted anilines, and eight substituted benzoic acids has been studied in dimethyl sulfoxide solutions by mcans of '"Co nmr. For the phenols substantial changes in the chemical shifts and in the linc widths are obscrvcd and are attributed to hydrogen bonding interactions. Effective equilibrium constants and chemical shifts for the hydrogcn bondcd species have been calculated. Thc equilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…They suggest that hydrogen bonding between the coordinated water and the cyanide groups of the incoming ligand may be important in stabilizing the outer sphere complex. The evidence for hydrogen bonded second sphere complexes with the same hexacyanometalates obtained by 59Co NMR and IR spectroscopy reported in the previous section of this review [71][72][73] provides some support for this interpretation. Further support is provided by the results of Ewen and Darensbourg [6] who obtained IR evidence for hydrogen bonding between cobaloximes and piperidine and suggested that this outer sphere complex could act as an intermediate in an Ia ligand substitution mechanism.…”
Section: The Mechanistic Role Of Outer Sphere Complexessupporting
confidence: 72%
See 1 more Smart Citation
“…They suggest that hydrogen bonding between the coordinated water and the cyanide groups of the incoming ligand may be important in stabilizing the outer sphere complex. The evidence for hydrogen bonded second sphere complexes with the same hexacyanometalates obtained by 59Co NMR and IR spectroscopy reported in the previous section of this review [71][72][73] provides some support for this interpretation. Further support is provided by the results of Ewen and Darensbourg [6] who obtained IR evidence for hydrogen bonding between cobaloximes and piperidine and suggested that this outer sphere complex could act as an intermediate in an Ia ligand substitution mechanism.…”
Section: The Mechanistic Role Of Outer Sphere Complexessupporting
confidence: 72%
“…Similar lifetimes have been obtained for H bond breaking in amines [69,70]. Hydrogen bonding between phenols, anilines and organic acids and the hexacyanocobaltate(HI) anion has been studied by 59Co NMR and by IR spectroscopy [71][72][73]. These studies also provided evidence for very short lifetimes of between 10 -° s and 10 -12 S. At the latter limit broadening of vibrational bands becomes possible.…”
Section: K= Yayb/ybyasupporting
confidence: 59%